ANALYSIS OF STUDIES ON THE ISSUE OF IMPROVING THE TECHNOLOGY OF DOUBLE TORSION - Yakubov Nosirjon Jurayevich (European Science Publishing, 2023)
The article obtained an analytical dependence of the tension of the wound thread on the filling parameters of the winding-unwinding device. The influence of the design features of the capsular tensioner on the thread tension in the production of twisted thread is determined. The possibility of performing backup winding on turns, the role of an automatic compensator for fluctuations in the thread tension between the main zones of the turn, caused by thread defects, has been established.
Keywords: textile materials, light industry, technological processes, high-quality yarn, double twist.